Identification of lactic acid bacteria from lemea's to lower blood sugar levels in mice's diabetes mellitus - Okfrianti, Yenni; Herison, Catur; Fahrurrozi, Fahrurrozi; Budianto, Budianto; Okticah, Anggi; Sari, Miliza Mayang (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2025)
Background: Diabetic is one of the main health problems in society throughout the world, so alternatives are needed to help prevent increasing blood sugar levels. In this case, lactic acid bacteria (LAB) are able to inhibit the performance of the alpha glucosidase enzyme in breaking down carbohydrates into glucose, lowering blood sugar levels so that lactic acid bacteria have potential in controlling hyperglycemia.Objectives: The purpose of this work is to assess the potential of four different strains of Lactobacillus that were isolated from lemea to reduce blood sugar levels in mice.Materials and Methods: This study used a pre-test, post-test, control group design for its experimental methodology. Six groups of 18 male mice, aged between 10 and 12 weeks, with body weights ± 25 g each, were formed,three mice comprised each group. This study was divided into 6 treatment groups, namely 1 group given acarboce, 1 group without treatment (aquadest), and 4 treatment groups given 4 types of pure BAL culture. Treatment consisted of P1 (giving L plantarum B1), P2 (giving L plantarum B2), P3 (giving L plantarum S1), and P4 (giving L fermentum S2). The initial stage of the research was to measure the initial fasting blood sugar of the mice, then alloxan was induced at a dose of 4.54 mg/kg BW and given intravenously at 0.1/10 g BW to the mice. After 5 days of alloxan induction, the fasting blood sugar level was measured again. If the blood sugar level was ≥ 127 mg/dL, the mice were declared DM and ready to be given treatment. The dose of acarbose was 0.65 mg/kg bw, and BAL culture with a concentration of 10 8 CFU/mL of 0.1 mg/ 10 g bw for 14 days every 7 days analyzed the blood sugar levels of the mice.Results: The results of the study showed that giving pure culture of L. plantarum from Betung bamboo shoot lemea to mice with type 2 diabetes mellitus (type 2 DM) as treatment P2 was superior to giving acarbose, P1, P3, and P4 in reducing blood sugar levels with pancreatic damage 50% and lower than other treatments, while the pancreas of type 2 DM mice without therapy had the greatest damage score based on histopathological data.Conclusion: Lactic acid bacteria from Lemea can help lower blood sugar levels and prevent the rate of damage to the pancreas of diabetic mice, with the best culture being L. plantarum from Lemea Betung bamboo shoots